2017
DOI: 10.29252/jafm.73.245.27878
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Tip Vortex Meandering in the Near Wake of a Horizontal-Axis Wind Turbine

Abstract: The aerodynamic optimization of horizontal axis wind turbine has became one of the most important challenge in the renewable energy field. Over the past few years, many researchers have drawn more attention to the physical processes of the wind energy conversion and precisely the identification of the main causes of energy losses. This paper presents an experimental investigation of near wake dynamics for a model horizontal axis wind turbine in a wind tunnel. The coherent structures downstream of the rotor wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In this section, the numerical results will be validated using the experimental results obtained in the CRTEn wind tunnel by Dahmouni et al (2017). They conducted an experimental study to analyze the meandering phenomenon of tip vortices in the near wake of a three-bladed HAWT model for different tip speed ratios λ= [3.50 -5.22].…”
Section: Validation Of the Obtained Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the numerical results will be validated using the experimental results obtained in the CRTEn wind tunnel by Dahmouni et al (2017). They conducted an experimental study to analyze the meandering phenomenon of tip vortices in the near wake of a three-bladed HAWT model for different tip speed ratios λ= [3.50 -5.22].…”
Section: Validation Of the Obtained Resultsmentioning
confidence: 99%
“…The first one was the limit of mesh grid number related to the station computing capacities and the second reason was the meandering phenomenon of the tip vortices which is defined as an instantaneous fluctuation of the vortex core position (Devenport et al 1996;Roy et al 2011). In wind turbine case, as mentioned by (Bandyopadhyay et al 1991;Sherry et al 2013a,b andDahmouni et al 2017), the meandering phenomenon is due to the instantaneous changes in the vortex strength, the helical nature of the vortex tubes and the interaction between instabilities in the wake. However, no offset was observed for the first tip vortex because the meandering phenomenon increases as the vortices are far away from the rotor where the interactions between the tip vortices and the wake becomes more critical.…”
Section: Fig 5 Velocity Profiles At Different Positions Behind the Rmentioning
confidence: 99%
“…Furthermore, Mula and Tinney (2014) and Dahmouni et al (2017) both indicated that kinetic energy is commonly adopted as a convergence criterion for the POD Snapshot method. The reduced-order POD model obtained can be utilized to reconstruct a velocity map with the majority of details that characterize flow behavior.…”
Section: Proper Orthogonal Decomposition Analysismentioning
confidence: 99%
“…The results of large eddy simulation showed that the dimensionless mean velocity and Reynolds stress curves in the wake of HAWT show selfsimilarity through an appropriate choice of characteristic scales of velocity and length. In recent years, numerous efforts have been spent on the wake characteristics and the establishment of wake models for HAWTs (Noura et al 2016;Belkheir et al 2012;Dahmouni et al 2017;Kabir et al 2019;Qian et al 2022). However, the research on the wake characteristics of VAWT is not as extensive as that of HAWTs (Paraschivoiu 2002).…”
Section: Introductionmentioning
confidence: 99%